Genome‐wide survey of transcriptional initiation in the pathogenic fungus, Candida glabrata. (14th April 2014) - Aoyama, Toshihiro; Nakayama, Hironobu; Ueno, Keigo; Inukai, Tatsuya; Tanabe, Koichi; Nagi, Minoru; Bard, Martin; Chibana, Hiroji
<x xml:space="preserve">Abstract</x> DNA sequencing of the 5′‐flanking region of the transcriptome effectively identifies transcription initiation sites and also aids in identifying unknown genes. This study describes a comprehensive polling of transcription start sites and an analysis of full‐length complementary DNAs derived from the genome of the pathogenic fungus Candida glabrata. A comparison of the sequence reads derived from a cDNA library prepared from cells grown under different culture conditions against the reference genomic sequence of the Candida Genome Database (CGD: http://www.candidagenome.org/) revealed the expression of 4316 genes and their acknowledged transcription start sites (TSSs). In addition this analysis also predicted 59 new genes including 22 that showed no homology to the genome of Saccharomyces cerevisiae, a genetically close relative of C. glabrata. Furthermore, comparison of the 5′‐untranslated regions (5′‐UTRs) and core promoters of C. glabrata to those of S. cerevisiae showed various global similarities and differences among orthologous genes. Thus, the C. glabrata transcriptome can complement the annotation of the genome database and should provide new insights into the organization, regulation, and function of genes of this important human pathogen.